Sustainable Protein‐Based Binder for Lithium‐Sulfur Cathodes Processed by a Solvent‐Free Dry‐Coating Method. Issue 22 (20th October 2022) - Schmidt, Florian; Kirchhoff, Sebastian; Jägle, Karin; De, Ankita; Ehrling, Sebastian; Härtel, Paul; Dörfler, Susanne; Abendroth, Thomas; Schumm, Benjamin; Althues, Holger; Kaskel, Stefan
Abstract: In the market for next‐generation energy storage, lithium‐sulfur (Li−S) technology is one of the most promising candidates due to its high theoretical specific energy and cost‐efficient ubiquitous active materials. In this study, this cell system was combined with a cost‐efficient sustainable solvent‐free electrode dry‐coating process (DRYtraec®). So far, this process has been only feasible with polytetrafluoroethylene (PTFE)‐based binders. To increase the sustainability of electrode processing and to decrease the undesired fluorine content of Li−S batteries, a renewable, biodegradable, and fluorine‐free polypeptide was employed as a binder for solvent‐free electrode manufacturing. The yielded sulfur/carbon dry‐film cathodes were electrochemically evaluated under lean electrolyte conditions at coin and pouch cell level, using the state‐of‐the‐art 1, 2‐dimethoxyethane/1, 3‐dioxolane electrolyte (DME/DOL) as well as the sparingly polysulfide‐solvating electrolytes hexylmethylether (HME)/DOL and tetramethylene sulfone/1, 1, 2, 2‐tetrafluoroethyl‐2, 2, 3, 3‐tetrafluoropropyl ether (TMS/TTE). These results demonstrated that the PTFE binder can be replaced by the biodegradable sericin as the cycle stability and performance of the cathodes was retained. Abstract : Green binder : The polypeptide sericin is introduced as a binder for solvent‐free manufactured S/C cathodes via the DRYtraec® process. Their electrochemical performance is evaluated under lean electrolyte conditions at coin and pouch cell level, with ether‐ or sulfolane‐based electrolytes. It is demonstrated that the established polytetrafluoroethylene binder can be successfully replaced with the fluorine‐free sericin.